Real-time computational fluid dynamics flow response visualisation and interaction application based on augmented reality - Sanderasagran, Ashwindran Naidu; Abd Aziz, Azizuddin; Daing Idris, Daing Mohamad Nafiz (Universiti Utara Malaysia Press, 2020)
The behaviour of fluid flow is a complex paradigm for cognitive interpretation and visualisation. Engineers need to visualise the behaviour mechanics of flow field response in order to enhance the cognitive ability in problem solving. Therefore, mixed reality related technology is the solution for enhanced virtual interactive learning environment. However, there are limited augmented reality platforms on fluid flow interactive learning. Therefore, an interactive education application is proposed for students and engineers to interact and understand the complex flow behaviour pattern subjected to elementary geometry body relative to external flow. This paper presented the technical development of a real-time flow response visualisation augmented reality application for computational fluid dynamics application. It was developed with the assistance of several applications such as Unity, Vuforia, and Android. Particle system modules available in the Unity engine were used to create a two-dimensional flow stream domain. The flow visualisation and interaction were limited to two-dimensional and the numerical fluid continuum response was not analysed.The physical flow response pattern of three simple geometry bodies was validated against ANSYS simulated results basedon visual empirical observation. The particle size and number of particles emitted were adjusted in order to emulate the physical representation of fluid flow. Colour contour was set to change according to fluid velocity. Visual validation indicated trivial dissimilarities between FLUENT generated results and flow response exhibited by the proposed augmented reality application.